Optimization of Inulin Hydrolysis by Penicillium lanosocoeruleum Inulinases and Efficient Conversion Into Polyhydroxyalkanoates - Corrado, Iolanda; Cascelli, Nicoletta; Ntasi, Georgia; Birolo, Leila; Sannia, Giovanni; Pezzella, Cinzia (Frontiers in Bioengineering and Biotechnology, 2021)
Inulin, a polydisperse fructan found as a common storage polysaccharide in the roots of several plants, represents a renewable non-food biomass resource for the synthesis of bio-based products. Exploitation of inulin-containing feedstocks requires the integration of different processes, including inulinase production, saccharification of inulin, and microbial fermentation for the conversion of released sugars into added-value products. In this work paper, a new microbial source of inulinase, Penicillium lanosocoeruleum, was identified through the screening of a fungal library. Inulinase production using inulin as C-source was optimized, reaching up to 28 U mL–1 at the 4th day of growth. The fungal inulinase mixture (PlaI) was characterized for pH and temperature stability and activity profile, and its isoenzymes composition was investigated by proteomic strategies. Statistical optimization of inulin hydrolysis was performed using a central composite rotatable design (CCRD), by analyzing the effect of four factors. In the optimized conditions (T, 45.5°C; pH, 5.1; substrate concentration, 60 g L–1; enzyme loading, 50 U gsubstrate–1), up to 96% inulin is converted in fructose within 20 h. The integration of PlaI in a process for polyhydroxyalkanoate (PHA) production by Cupriavidus necator from inulin was tested in both separated hydrolysis and fermentation (SHF) and simultaneous saccharification and fermentation (SSF). A maximum of 3.2 g L–1 of PHB accumulation, corresponding to 82% polymer content, was achieved in the SSF. The proved efficiency in inulin hydrolysis and its effective integration into a SSF process pave the way to a profitable exploitation of the PlaI enzymatic mixture in inulin-based biorefineries.